Pengaruh Branding Strategic pada Sweet and Salt Padang dalam Meningkatkan Penjualan - Feronica Della Puspita; Raisha Andriani; Nurul Kholifah (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2025)
Changes in the lifestyles of the younger generation in Padang City have significantly contributed to the growth of the culinary and entertainment sectors, especially in services for birthday celebrations and small banquets presented in aesthetic and personalized packages. In this highly competitive culinary business, a strong branding strategy is essential for building a recognizable brand image and attracting consumers. Improving product quality and quantity, diversifying offerings, and providing a wide variety of products are critical for creating added value and expanding market share. Equally important, effective promotion enables companies to communicate with consumers, influence purchasing decisions, and strengthen brand loyalty. The general equilibrium concept offers a framework to understand how interconnected markets respond to changes in supply, demand, and consumer preferences, highlighting the need for businesses to continuously evaluate and adapt their strategies. This study emphasizes that success in Padang City’s bakery and culinary service industry depends on the integration of branding strategies, ongoing product development, and targeted promotional efforts, ensuring competitiveness, customer satisfaction, and sustainable business growth.